2020
DOI: 10.4103/jmu.jmu_29_20
|View full text |Cite
|
Sign up to set email alerts
|

Fetal epicardial fat thickness: Can it serve as a sonographic screening marker for gestational diabetes mellitus?

Abstract: Background: Gestational diabetes mellitus (GDM) is defined as the new onset of impairment in carbohydrate tolerance during pregnancy. The aim of the current study was to define fetal epicardial fat thickness (fEFT) changes that developed before 24 weeks of gestation, to evaluate the diagnostic effectiveness of fEFT in predicting GDM diagnosis, and to correlate fEFT values with hemoglobin A1C (HbA1C) values. Methods: The study included a total of 60 GDM patients and 60 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
2
13
2
Order By: Relevance
“…The fetus absorbs glucose, stores it in the form of glycogen in the liver, and the excess is converted into visceral fat, increasing the fetal abdominal circumference. Moreover, fetal epicardial fat thickness has been proposed as an earlier marker (before 24 weeks) to screen GDM women [ 314 ]. Macrosomia and hyperglycemia predispose to obstetrics complications such as shoulder dystocia at birth, plexus-brachial injury, respiratory distress syndrome, as well as the need for instrumented delivery [ 7 , 315 ].…”
Section: Adverse Perinatal Outcomes Related To Gdmmentioning
confidence: 99%
“…The fetus absorbs glucose, stores it in the form of glycogen in the liver, and the excess is converted into visceral fat, increasing the fetal abdominal circumference. Moreover, fetal epicardial fat thickness has been proposed as an earlier marker (before 24 weeks) to screen GDM women [ 314 ]. Macrosomia and hyperglycemia predispose to obstetrics complications such as shoulder dystocia at birth, plexus-brachial injury, respiratory distress syndrome, as well as the need for instrumented delivery [ 7 , 315 ].…”
Section: Adverse Perinatal Outcomes Related To Gdmmentioning
confidence: 99%
“…This increase can be detected even at 24 wk of gestation. In addition, foetal EFT values are positively correlated with HbA1c values and can be an early predictor for gestational DM diagnosis[ 46 ].…”
Section: Cardiac Evaluation Of Foetuses and Idmsmentioning
confidence: 99%
“…In the other study by Aydın et al fetal EFT measurements were performed at 18-22 weeks of gestation. 25 They showed that the fetal EFT values of GDM patients were significantly higher than those of the control group. Moreover, correlation analysis showed that a strong positive correlation was observed between fetal EFT and Hba1c values and EFW.…”
Section: Discussionmentioning
confidence: 97%
“…20,21 There are few studies that investigated the measurement of EFT in fetuses of mothers with GDM. [22][23][24][25] The need for markers that can help predict the occurrence of GDM and the increased risk of GDM-related perinatal complications remains one of the main topics of current studies. Because previous studies have shown that the increase in fetal adipose tissue in fetuses with GDM occurs most frequently in the 3rd trimester, we aimed to compare fetal EFT in the 3rd trimester in cases diagnosed with GDM with fetuses from healthy mothers.…”
Section: Introductionmentioning
confidence: 99%